DEVELOPMENT OF A 3D PRINTER SCREW EXTRUDER THAT USES GRANULES OR CRUSHED POLYMER PARTICLES AS RAW MATERIALS - ПОЛІЩУК, А. О. (Technologies and Engineering, 2024)
Purpose. Development of a 3D printer screw extruder design that uses granules or crushed polymer particles as raw materials and provides an accurate and stable polymer extrusion process for 3D printing models. Methodology. The method of systematic, theoretical and comparative analyzes was used in the work. Theoretical and practical studies are based on fundamental principles and knowledge in the field of mechanical engineering, heat engineering, and also take into account the features and requirements related to polymer processing, ensuring the efficiency of this process. Findings. An overview of the methods of manufacturing products and parts was conducted and the additive method was substantiated as promising for creating products by 3D printing. Different types and approaches to additive manufacturing based on extrusion are considered and it is proposed to use a screw in an extruder that prints with granules or crushed polymer particles. The geometry of the micro-screw has been developed, which optimizes the process of melting and feeding polymeric materials, increasing the quality of printing and reducing the time of extrusion. The design of the loading hopper has been improved, which ensures uniform and effective feeding of granules and crushed polymer particles into the material cylinder by a rotating auger. A cooling system for the extruder body and loading hopper has been developed. A nozzle with an internal geometry that optimizes the flow of molten polymer and increases printing accuracy is designed. A developed screw extruder is installed instead of a filament printing extruder on a 3D printer. The operation of the main elements of the 3D printer was synchronized with the developed extruder and their modes of operation were optimized. The process of printing test samples and finished parts using the developed screw extruder was carried out. Originality. An extruder with a rotating micro-screw for a 3D printer that prints granules or particles of crushed polymer has been developed. The operation of the proposed screw extruder was synchronized with the elements of the 3D printer, which ensured high print quality, reliability and overall efficiency of the equipment after improvement. Practical value. Using pellets or chopped pieces of polymer can be significantly cheaper than using traditional filament. This makes 3D printing more affordable and cost-effective, especially for large-scale production. The use of recycled materials contributes to the improvement of environmental safety, allows to reduce the volume of polymer waste. A screw extruder allows the use of a wider range of polymer materials, including polymers that may not be suitable for filament printing. The development of a screw extruder for a 3D printer opens new horizons in the practical use of 3D printing, providing more cost-effective, environmentally sustainable and innovative solutions for various fields of application.